2016
DOI: 10.1007/s00394-016-1220-2
|View full text |Cite
|
Sign up to set email alerts
|

Choline and polyunsaturated fatty acids in preterm infants’ maternal milk

Abstract: This study was registered at www.clinicaltrials.gov. Identifier: NCT01773902.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 44 publications
6
32
3
Order By: Relevance
“…Consistent with previous studies [6,11,12], PhosC and GPC were the major choline forms in both preterm and donor milk samples, and the proportions of WSC compounds did not seem to vary by milk group. In our study, PhosC ranged between 57%–59%, GPC between 27%–30%, and FC between 13%–16% of the total milk WSC compounds.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previous studies [6,11,12], PhosC and GPC were the major choline forms in both preterm and donor milk samples, and the proportions of WSC compounds did not seem to vary by milk group. In our study, PhosC ranged between 57%–59%, GPC between 27%–30%, and FC between 13%–16% of the total milk WSC compounds.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, this may be explained by the pooling of milk from various donors to produce a larger batch of pasteurized donor milk. Additionally, total WSC concentration seems to vary across lactation [12] and a wide difference in lactation age between the two milk groups may be a contributing factor. We are limited by lack of data on the age of infants at the time their mothers donated milk used in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have indicated the utility of adding choline to infant feed (111). The addition of choline, as well as melatonin, to infant feeding requires investigation, especially as to whether there are any synergistic effects, including in the gut and in the regulation of the gut-brain axis, as preclinical data would suggest (39).…”
Section: Melatonin Addition To Formula Feedmentioning
confidence: 99%